2019
DOI: 10.1007/s00431-019-03425-5
|View full text |Cite
|
Sign up to set email alerts
|

Can digital X-ray radiogrammetry be an alternative for dual-energy X-ray absorptiometry in the diagnosis of secondary low bone quality in children?

Abstract: Bone quality in children is generally measured with dual-energy X-ray absorptiometry (DXA). Digital X-ray radiogrammetry (DXR) uses BoneXpert to measure cortical bone quality on hand radiographs. This prospective study compared DXR and DXA results in children with high probability of secondary low bone quality, defined as DXA of the lumbar spine (DXA LS ) Z -score ≤ − 2.0. One hundred one children underwent both DXA and DXR assessment. DXA LS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…DXR results were found to correlate well with BMD measurements by DXA in middle-aged and elderly women [ 37 ]. In children, BHI SDS has showed strong correlations with areal and height-adjusted BMD measurements by DXA, including low DXA values of z < –2 [ 38-42 ]. Similar correlations have been observed between BHI SDS and total BMD as assessed via pQCT [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…DXR results were found to correlate well with BMD measurements by DXA in middle-aged and elderly women [ 37 ]. In children, BHI SDS has showed strong correlations with areal and height-adjusted BMD measurements by DXA, including low DXA values of z < –2 [ 38-42 ]. Similar correlations have been observed between BHI SDS and total BMD as assessed via pQCT [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secondary form and secondary low bone quality in children is due to systemic disease, their treatment, or indirect effects of systemic disease such as immobilization, poor nutrition etc. The course of osteoporosis in children is different than in adults due to varying bone mass (bone mass density, BMD) with age (18).…”
Section: Digital X-ray Radiogrammetry (Dxr)mentioning
confidence: 99%
“…To assess bone health on digital radiographs, different parameters have been proposed such as the Bone Health Index® (BHI) [ 84 , 85 ]. Studies comparing BHI determined by X-ray and BMD assessed by DXA showed contradictory results [ 86 92 ]. BHI seems to overestimate bone health impairment, also, the correlation with DXA measurements is not always good as it applies mainly to absolute values than to Z -scores.…”
Section: Diagnostic Techniques To Assess Bone Healthmentioning
confidence: 99%